THE EFFECT OF INFLATION, INTEREST RATE AND COVID-19 PANDEMIC ON RUPIAH EXCHANGE RATE 2009-2023 - Rahman, Abdul; Syapsan, Syapsan; Widyatsari, Any (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2024)
This study aims to determine the effect of inflation, interest rates, and Covid-19 pandemic on rupiah exchange rate during the period from 2009 to 2023. This research utilizes secondary data obtained from Bank Indonesia and employs multiple linear regression analysis method with the assistance of SPSS software version 29.0. The research findings indicate that inflation has a positive and significant effect on the exchange rate of the rupiah, while interest rates have a negative and significant effect on the exchange rate of the rupiah. Additionally, the Covid-19 pandemic (as a dummy variable) has a positive and significant effect on the exchange rate of the rupiah. The Coefficient of Determination (R2) is 0.566, meaning that 56.6% of the variability in the exchange rate of the rupiah can be explained by inflation, interest rates, and the Covid-19 pandemic. Furthermore, the variable most dominant in influencing the exchange rate of the rupiah is inflation, accounting for 39.9%